Lectures and Essays - Smith, Goldwin, 1823-1910 (Salt Lake City, UT : Project Gutenberg, 2004)
"Lectures and Essays" by Goldwin Smith is a historical and political collection of writings produced during the late 19th century. This compilation focuses on various topics, including the analysis of historical events, literature, and the impact of certain figures on society, revealing an interest in Canada$1 (Bs literary contributions and reflections on political themes. At the start of the work, the prefatory note outlines Smith's intent to compile these essays and lectures for friends who have expressed interest in previously published materials. The opening essay, titled "The Greatness of the Romans," delves into the factors that contributed to Rome's rise to power while questioning the traditional narratives that attribute their success primarily to military might. Smith argues for a deeper examination of geographical advantages, the evolution of political structures, and the significance of discipline in warfare, setting the stage for discussions that would shed light on the broader nature of historical interpretation and its relevance to contemporary society. (This is an automatically generated summary.)s
The greatness of the Romans -- The greatness of England -- The great duel of the seventeenth century -- The lamps of fiction; a speech on the centenary of the birth of Sir Walter Scott -- An address to the Oxford school of science and art -- The ascent of man -- The proposed substitutes for religion -- The labour movement -- What is culpable luxury? -- A true captain of industry [Mr. Brassey] -- A wirepuller of kings [Baron Stockmar] -- The early years of the conqueror of Quebec -- Falkland and the Puritans -- The early years of Abraham Lincoln -- Alfredus Rex Fundator -- The last republicans of Rome -- Austen-Leigh's memoir of Jane Austen -- Pattison's Milton -- Coleridge's life of Keble.
Release date is 2004-09-01
Produced by Tonya Allen, Juliet Sutherland, Charles Franks and the Online Distributed Proofreading Team
Keywords: Canadian essays -- 19th century